Sayyid Ahmad Khan Bapak pendidikan dari India - Ummah, Rohmatul (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
Sayyid Ahmad Khan is one of the fathers of education who is very influential on the progress of Islamic education where his thinking about education, religion and social matters greatly influences the process of change in accordance with the demands of the times. He purified the teachings of Islam which were adapted to the context of modern society without removing moral and religious values.